A Research on the Relation of Religion and Healing in Ancient Greece - Alakuş, Abdullah (Erciyes Üniversitesi, 2021)
The fact of religion has been at the center of humanity life since its first days. Religious factors were also at the center of the searching and expectation of healing in association with the religious beliefs of societies and treatment methods were developed in that context. However, it is seen that this attitude has changed in the historical process due to tangible and abstract developments provided by humanity. The origins of this change are considered to be based on scientific and intellectual events that developed in the 6th and 5th centuries B.C. in Ancient Greek civilization. In Ancient Greece, it is seen that two different approaches were adopted periodically to diseases and their treatments. First one is the mythological/supernatural or religious approach that has existed since the earliest times in human history. The other one is the rational approach that developed with the Hippocrates school. In the Greeks, both healing concepts have been applied as a treatment method throughout centuries. In the Hippocrates school, instead of religious elements, disturbance of the balance based on the theory of four fluids that thought to be found in the human body and natural causes such as environmental factors were accepted as source of diseases. It is also seen that the Hippocrates school criticizes the magical treatment approach among the people. In this study, it will be tried to be evaluated whether there is a contradiction between religious beliefs in Ancient Greece and two different healing conceptions and what kind of a connection between them.

Din olgusu insanlığın ilk günlerinden itibaren hayatlarının merkezinde yer almıştır. Toplumların dini inançlarıyla bağlantılı olarak şifa arayışının ve beklentisinin odağında da dinsel unsurlar olmuş ve bu bağlamda tedavi yöntemleri geliştirilmiştir. Ancak insanlığın sağladığı maddi ve manevi gelişmeler sonucunda bu tutumun tarihsel süreç içerisinde değişime uğradığı görülmektedir. Bu değişimin kökenlerinin, Eski Yunan medeniyetinde MÖ VI. ve V. yüzyılda gelişen bilimsel ve düşünsel bulgulara dayandığı kabul edilmektedir. Eski Yunanda dönemsel olarak hastalıklara ve tedavilerine öz itibariyle iki farklı yaklaşımın benimsendiği görülmektedir. Bunlardan ilki insanlık tarihinde ilk dönemlerden itibaren bulunan mitolojik/doğaüstü ya da dinsel yaklaşımdır. Diğeri ise Hipokrat ekolüyle birlikte gelişen akılcı yaklaşımdır. Yunanlılarda, her iki şifa anlayışı da yüzyıllar boyunca bir tedavi yöntemi olarak uygulanmıştır. Hipokrat ekolünde, hastalıkların kaynağı olarak dini unsurlardan ziyade insan vücudunda bulunduğu düşülen dört sıvı teorisine dayanan dengenin bozulması ve çevresel faktörler gibi doğal nedenler kabul edilmiştir. Ayrıca Hipokrat ekolü tarafından halk arasında bulunan sihirsel ve büyüsel tedavi anlayışının eleştirildiği görülmekledir. Bu çalışmada Eski Yunandaki dinsel inançlar ile var olan iki farklı şifa anlayışının çelişip çelişmediği ve aralarında nasıl bir bağ olduğu değerlendirilmeye çalışılacaktır.
Eski Yunan’da Din ve Şifa İlişkisi Üzerine Bir Araştırma